Implementasi Total Quality Management untuk meningkatkan mutu pendidikan di Madrasah Tsanawiyah Ma'arif Darussholihin Sumberadi Mlati Sleman - Rahmadani, Luthfi Setya; Soddiq, Muhammad Ja’far (Indonesian Journal of Educational Management and Leadership, 2023)
The purpose of this study is to find out in depth the process of running Total Quality Management (TQM) in Islamic educational institutions, namely located at madrasah Tsanawiyah Ma'arif Darussholihin Sumberadi Mlati Sleman Yogyakarta. The research uses qualitative research methods with a Descriptive approach method that explains phenomena and circumstances as they are. The method of data collection uses interviews, observations, and documentation. The data analysis method uses data reduction, display data, and Drawings/Verification. From the results of this study, it is explained that the implementation of TQM in MTs Darussholihin leads to aspects of improving the quality of learning, increasing the professionalism of employees, maintaining good relations with customers and leading to aspects of products produced by MTs Darussholihin. Supporting factors in the implementation of TQM in MTs Darussholihin are: first, the existence of the Tahfidzul Qur'an program as a representative form of MTs Darussholihin's vision, namely producing a generation of tahfidzul Qur'an who is intelligent, independent and creative. Both environments are conducive to learning activities because MTs Darussholihi stands in the Ash Sholihah Islamic boarding school complex. The inhibiting factors in the implementation of TQM in MTs Darussholihin are: first, the slow development of all infrastructure both leading to facilities and infrastructure that are supporting components in learning activities in madrasahs. Second, the lack of human resources who are the driving component in the implementation of learning in madrasah